European Union and the Treaty on the Prohibition of Nuclear Weapons - Adviye Damla Ünlü (Akademik İncelemeler Dergisi)
United Nations General Assembly (UNGA) adopted the Treaty on the Prohibition of Nuclear Weapons (TPNW) on July 7, 2017. The Treaty is a legal instrument that highlights the humanitarian aspect of nuclear disarmament and provides an alternative to the disarmament approach of the Non-Proliferation Treaty (NPT). Because this Treaty sought to eliminate nuclear weapons, nuclear-weapon states (NWS) and states whose security is based on nuclear deterrence, criticized it for weakening the NPT. However, particular states and supranational nongovernmental organizations, such as the International Campaign for the Elimination of Nuclear Weapons (ICAN) opposed nuclear proliferation by carrying out an active, vigorous campaign to ban nuclear weapons and accomplish the goals of the TPNW. Here, two opposing sides emerged on this rather current issue. This study examines the potential of the European Union (EU) which has members from both sides and has policies towards non-proliferation and controlling nuclear weapons since its foundation, to lead and advance the movement of the ban of nuclear weapons, namely the TPNW process. The study intends to determine the strengths and weaknesses of the EU in its support and contribution to the TPNW process, conducting a further discussion on the issue.